The Influence of Government Debt on the Financial Position of the State (Economics and region, 2021)
The problem of external public debt has always been, and remains chronic for Ukraine. In the context of the corona crisis, this problem has acquired new, more complex shapes. A large number of countries, including Ukraine, find themselves in a situation of shortage of financial resources, it takes more than one year for economic recovery. To stabilize the situation, attracting loans from foreign organizations, lenders, countries where there is excess capital has become the only possible alternative. The article analyzes the current state of Ukraine's external debt. It is revealed the rapid growth of the external public debt of Ukraine. If the situation does not change, then Ukraine will need to attract additional foreign loans to pay off urgent obligations. This situation will only increase the burden on future generations and the state budget in the coming years. Today there is a high level of uncertainty regarding the state of the national economy of Ukraine and the possibility of effective management of external debt.
Keywords: public debt; security; financial security; debt; government